SAT0101 INTRAHOSPITAL MORTALITY IN PATIENTS WITH RHEUMATOID ARTHRITIS: OBSERVATIONAL STUDY AT THE NATIONAL LEVEL OVER A 17-YEAR PERIOD (TREND-AR STUDY). (June 2019) - Mazzucchelli, Ramón; Perez-Fernandez, Elia; Barbadillo, Carmen; Crespí-Villarías, Natalia; Fernandez-Prada, Manuel; Galindo-Izquierdo, María; García-Vadillo, Alberto; Godoy, Hilda; Varela, Angeles Herranz; Macía-Villa, Cristina; Quiroga, Concepción Morado; Morell Hita, Jose Luis; et al.
Abstract : Background: There have been important changes in the management of RA in the last 20 years, such as T2T strategy or new biologic agents. The potential impact of these therapeutic strategies on important objectives such as intrahospital mortality due to different causes is not known. Objectives: To analyze the incidence and tendency of mortality by different causes (global, cardiovascular, infectious, neoplasm, and others) in patients with RA, in Spain, during the period 1999-2015. Methods: Retrospective cohort study based on the exploitation of the database that collects a minimum basic set of data (MBDS) of all income in patients with RA. Period: 1999 to 2015. We analyzed cases of intrahospital death and the main diagnosis of these cases. The causes of death were identified by the presence of the corresponding ICD 9 codes in the main diagnostic fields. The causes of death in the hospital, global, by sex and in periods 1999-2001, 2003-2006, 2007-2010 and 2011-2015 are described. The results are expressed in absolute numbers and in proportion to the total number of deaths. Results: There was a total of 338, 343 hospital admissions in patients with RA during the 17 years of the study period, corresponding to a total of 176, 097 patients (117, 985 women and 58, 112 men). There was a total of 18, 641 hospital exitus (5.5% of the incomes). 63.4% were women. The mean age was 76.4 (SD 10.1) (in females of 77.2 (SD 10.2) and in men of 75.1 (SD 9.9) p <.001). The mean of Charlson index was 3.2 (SD 2.4). The mean age was increased linearly from 73.5 (1999-2002) to 78.23 (2011-215). The following table shows the causes of death grouped by sex and period: Conclusion: The main causes of intrahospital mortality in patients with RA in Spain were cardiovascular (24%), infections (20%), respiratory-non-infectious (15%) and neoplasms (12%). The average age of death increased 5 years in the study period. The deaths from infections, respiratory and neoplasms have increased, while those of digestive origin and AR extrarticular have decreased. Disclosure of Interests: None declared